Determinan Tingkat Bagi Hasil Simpanan Deposito Mudharabah - Kurniawan Kurniawan; Yohandi Yahya Pramono (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2016)
This research was conducted to test the influence of variable Return On Asset (ROA), operating costs operating income (BOPO), and Financing to Deposit Ratio (FDR) against the level of sharing Mudharabah deposits. System for the results is the system where the ill-fated agreement or bond together in performing business activities for example deposits Mudharabah on Cooperative BMT Al-Ikhlash East of Lumajang in 2010 – 2013. As for the variables examined is ROA (X1), BOPO (X2), FDR (X3) against the level of sharing Mudharabah deposits. In this research the secondary method used in Cooperative BMT Al-Ikhlash East of Lumajang. This analysis data processing techniques include: Classic assumption test, test multiple regression analysis, hypothesis testing with partial tests (test t), simultaneous testing (test F). The test results showed that partially Return On Asset and Financing To Deposit effect significantly to levels of Mudharabah deposits for the results. Meanwhile, operating expenses and operating income do not affect significantly the level of terhadp for results of Mudharabah deposits. The test results indicate that the simultaneous Return On assets, Financing To Deposit and operating expenses and operating income results for the level of influence on Mudharabah deposits.